Control of Rent Act 1966 critical study / Rozilah Salleh - Salleh, Rozilah (Faculty of Law, 1986)
The general purpose of the Rent Acts has always been to provide a safeguard against social and economics evils that are generated by a shortage of housing. The beginning of the Rent Acts therefore coincide with the housing shortage partly caused by the first world war and which followed that war. The question now seems to be, "Does the present housing situation in Malaysia justify the continuance of the existing law of Rent Control?" The purpose of this study is to examine and evaluate certain important aspects to the existing law on rent control in order to arrive at a conclusion whether rent control should be retained or abolished. In doing so, the writer attempts to expose some of the common fallacious attached to rent control, including the practical side.